2021
DOI: 10.1186/s12877-021-02695-9
|View full text |Cite
|
Sign up to set email alerts
|

Persistent polypharmacy and fall injury risk: the Health, Aging and Body Composition Study

Abstract: Background Older adults receive treatment for fall injuries in both inpatient and outpatient settings. The effect of persistent polypharmacy (i.e. using multiple medications over a long period) on fall injuries is understudied, particularly for outpatient injuries. We examined the association between persistent polypharmacy and treated fall injury risk from inpatient and outpatient settings in community-dwelling older adults. Methods The Health, Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…A systematic review found that 65–93% of patients admitted with a fall-related injury were on FRIDs at the time of hospitalisation [ 11 ]. Polypharmacy that includes FRIDs was associated with increased risk for fall injuries that require medical care [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review found that 65–93% of patients admitted with a fall-related injury were on FRIDs at the time of hospitalisation [ 11 ]. Polypharmacy that includes FRIDs was associated with increased risk for fall injuries that require medical care [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deprescribing FRIDs could be a possible preventive measure in older people and an important component of falls prevention programmes, along with other health and environmental safety measures [ 23 ]. Such interventions might reduce the risk of falls injuries that require medical treatment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Injuries from these falls are associated with substantial morbidity and mortality in the geriatric population, causing both fatal and non-fatal injuries (Ziere et al 2006 ; Zia et al 2015 ). Almost 33% of individuals 65 years of age and older and 50% of individuals over 80 will experience a fall annually, suggesting that injuries related to these falls are becoming a public health concern that must not go overlooked (Xue et al 2021 ; Smith et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies (Davies et al 2020 ; Ziere et al 2006 ; Zia et al 2015 ; Xue et al 2021 ) have demonstrated the association between falls and polypharmacy in the elderly population. Although there is substantial evidence for improved clinical outcomes from disease-specific medications, the cumulative side effect profile may contribute to the increased incidence of falls and, potentially, lead to increased morbidity and mortality associated with trauma injuries in the geriatric population (Moreland et al 2020 ; Zia et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Falls studies have determined that taking ≥4 drugs is associated with an increased incidence of falls, recurrent falls, and injurious falls ( Zia et al, 2015 ). The Health, Aging and Body Composition Study included 1764 community-dwelling adults demonstrated polypharmacy, particularly combined with fall risk increasing drugs use, was associated with increased risk for treated fall injuries from inpatient and outpatient settings ( Xue et al, 2021 ). Therefore, the cautious use of fall risk increasing drugs is critical for reducing the occurrence of falls.…”
Section: Introductionmentioning
confidence: 99%